Effects of electroacupuncture on experimental periodontitis in rats - Lisboa, Mario R. P.; Gondim, Delane V.; Ervolino, Edilson [UNESP]; Vale, Mariana L.; Frota, Nicolly P. R.; Nunes, Nara L. T.; Mariguela, Viviane C. [UNESP]; Taba, Mario; Messora, Michel R.; Furlaneto, Flavia A. C. (Amer Acad Periodontology, 2015)
Background: Acupuncture has shown the capability of modulating the immuno-inflammatory response of the host. This study aims to evaluate the effects of electroacupuncture (EA) on ligature-induced periodontitis in rats. Methods: Thirty-two animals were divided into four groups: 1) control; 2) experimental periodontitis (EP); 3) sham-treated (EP/EA-sham); and 4) treated with EA (EP/EA). For the EP groups, a ligature was placed around the right mandibular first molars at day 1. Sessions of EA or EA-sham were assigned every other day. For EA treatment, large intestine meridian points LI4 and LI11 and stomach meridian points ST36 and ST44 were used. EA-sham was performed in off-meridian points. Animals were euthanized at day 11. Histomorphometric and microtomographic analyses were performed. Immunolabeling patterns for the receptor activator of nuclear factor kappa B ligand (RANKL), osteoprotegerin (OPG), and tartrate-resistant acid phosphatase (TRAP) were assessed. Expressions of interleukin (IL)-1 beta, matrix metalloproteinase (MMP)-8, IL-6, and cyclooxygenase (COX)-2 messenger RNAs (mRNAs) were evaluated by quantitative reverse transcription-polymerase chain reaction. Data were analyzed statistically (P < 0.05, analysis of variance). Results: Histomorphometric and microtomographic analyses demonstrated that group EP/EA presented reduced alveolar bone loss when compared to group EP (P < 0.05). Reduced RANKL immunolabeling and fewer TRAP-positive multinucleated cells were observed in the EA-treated group in relation to group EP. No differences were observed in OPG expression among groups. EA treatment decreased the genic expression of IL-1 beta and MMP-8 (P < 0.05), increased the mRNA expression of IL-6 (P < 0.05), and did not modify the genic expression of COX-2 in animals with EP (P > 0.05). Conclusion: It can be concluded that EA reduced periodontal tissue breakdown and the expression of some proinflammatory mediators and a proresorptive factor in EP in rats.
Keywords: Bone resorption; Electroacupuncture; Inflammation mediators; Periodontitis